The correlation between principal’s leadership and conducive school culture with teachers’ productivity - Mahyudin (Nalar: Journal of Pedagogy and Society, 2021)
This study aims to determine the correlation of Principal Leadership and Conductive School Culture with Teacher Productivity at SMP Negeri Bangkinang District, Kampar Regency. This research was conducted on teachers at the State Junior High School, Bangkinang District, Kampar Regency. The data are collected by distributing questionnaire. To analyze the data, descriptive and Multiple Linear Regression are used. The results of this study indicate that there is a relationship between Principal Leadership and Conductive School Culture with Teacher Productivity at SMP Negeri Bangkinang District, Kampar Regency. The magnitude of the relationship between the Principal's Leadership on productivity is 38.7%, the magnitude of the conducive school culture relationship is 40.9%, and the joint relationship is 79.3%.